A Study on Determination Health Literacy Level and ldentification of Knowledge, Manner, Behavioral Change and Educational Needs of Elementary School Teachers (Turkey Health Literacy Journal, 2020)
Nowadays, individuals are expected to be able to recognize their own diseases, manage their chronic diseases, and make decisions that they think are good for them during the prevention and treatment process. The effectiveness, effectiveness and quality of health services also depend on the decisions of individuals receiving health care on their own health. Health Literacy; It is extremely important in terms of increasing the year and quality of healthy life in health services and eliminating health inequalities. Method: The population of this research, which was planned descriptively and cross- sectionally, was analyzed using TSOY-32 Health Literacy Scale by classroom teachers working in Sancaktepe district of Istanbul to 306 classroom teachers determined by randomization method between 15.05.2019 15.06.2019. There were 255 valid survey returns. Results: 35% of the participants had Problem-Limited Health Literacy, 17% had poor Health Literacy, 27% had Adequate, 21% had Excellent Health Literacy. 52.2% were in the 22-34 age range, 69.8% were married, 71.4% were women, 93.7% were bachelor’s degree; 11.4% have chronic disease. Discussion: Behavioral changes that may occur with the development of Health Literacy should be gained to people at an early age. Primary school age is an important opportunity for this. In this respect, class teachers are the ones who play the most important role. As a result of this study, it was found that the health literacy levels of classroom teachers were limited and problematic. Efforts should be made to increase the health literacy levels of classroom teachers.